The Importance of Speaking Skills in Learning Foreign Languages and Being Able to Apply Them into Practice - Qizi, Dushatova Shohsanam Baxtiyor; Qizi, Sultonalieva Makhbuba Alisher (International Journal on Integrated Education, 2023)
Today, everyone needs to acquire communication skills in order to achieve high goals in their fields. This article provides information about the main principles and various ways that help in teaching and learning foreign languages.